Hippocampal glutamate NMDA receptor loss tracks progression in Alzheimer's disease: quantitative autoradiography in postmortem human brain. - Efrat Kravitz; Inna Gaisler-Salomon; Anat Biegon (PLoS ONE, 2013)
Early Alzheimer's disease (AD) is characterized by memory loss and hippocampal atrophy with relative sparing of basal ganglia. Activation of glutamate NMDA receptors in the hippocampus is an important step in memory formation. We measured the density of NMDA receptors in samples of hippocampus, entorhinal cortex and basal ganglia obtained from subjects who died with pathologically confirmed AD and age- and sex- matched non-demented controls. We found significant decreases in NMDA receptor density in the hippocampus and entorhinal cortex but not in the basal ganglia. Loss of NMDA receptors was significantly correlated with neuropathological progression as assessed by Braak staging postmortem. The same samples were probed for neuroinflammation by measuring the density and gene expression of translocator protein 18 kDA (TSPO), an established marker of microglial activation. Unlike NMDA receptor loss, increased densities of TSPO were found in all of the brain regions sampled. However hippocampal, but not striatal TSPO density and gene expression were inversely correlated with NMDA receptor density and positively correlated with Braak stage, suggesting NMDA receptors exacerbate neuroniflammatory damage. The high correlation between hippocampal NMDA receptor loss and disease progression supports the use of non invasive imaging with NMDA receptor tracers and positron emission tomography as a superior method for diagnosis, staging and treatment monitoring of AD in vivo.